Pengaruh Komitmen dan Pendapatan Terhadap Kebersamaan Pegawai Negeri Sipil Di Kota Pekanbaru - Novita, Novita (Jurnal Daya Saing, 2015)
Abstract: Mental revolution for civil servants is an important part that is inseparable and as a form of an example for the private sector and civil society in order to build cohesiveness or togetherness. Not optimal sense of suspected dipengruhi by a factor of commitment and factor income. This research method using kunatitatif and analyzed with multiple linear regression statistical analysis. Penenlitian of results proved that the commitments and revenues provide positive and significant impact on the unity government employees in providing services to the public. Problems togetherness of employees is a form of mental changes and revolutions that need to get serious attention and become the focus means. Therefore, need support in various circles. Keywords: Commitment, Revenue and Togetherness